Lithuanian theatres during the COVID-19 pandemic: an eagerness to create and to watch - Petrikienė, Asta (Creativity Studies, 2023)
The unprecedented circumstances created by the COVID-19 pandemic significantly changed the usual processes of work throughout the creative industries. In case of theatre, the companies could no longer perform in the usual facilities and rehearsals were restricted. Theatre artists reacted differently to the new conditions dictated by the COVID-19 pandemic. Facing restrictions of working in contact mode some sought ways to adapt and not only create but also present performances to audiences online, others chose to deny the forms of mediatized theatre, as if waiting for the times to change. The aim of this article is to review the dynamics of theatre attendance in Lithuania in the 2018–2020 period. Data from yearly reports of state funded theatres reveal how many viewers visited Lithuanian theatres physically and how many performances were watched online. The analysis of this data provides an insight into the changes in the number of viewers compared to the pre-COVID-19-pandemic years and answers the question of whether performances on Internet platforms attracted a significant number of online audiences. The results of the analysis are indicative of the sustainability of the demand for views of performances online.